Assessment and management of radiotherapy induced toxicity in older patients. Issue 6 (November 2017) - O'Donovan, Anita; Leech, Michelle; Gillham, Charles
Abstract: Radiotherapy is an attractive treatment option for older adults, especially where surgery and chemotherapy pose too great a risk. Radiotherapy toxicity may be divided into acute/early and late effects of treatment. The latter may have limited relevance to an older patient with competing causes of mortality due to significant comorbidity. Altered fractionation regimes have been employed in numerous sites, with no significant toxicity impact. These offer greater convenience in the elderly, especially those with limited social support or in active caregiving roles. As radiotherapy toxicity is site specific, it's important to assess baseline function via Comprehensive Geriatric Assessment (CGA), and any pre-existing comorbidities that may influence toxicity. With modern radiotherapy technology and capabilities, these are less of an issue and radiotherapy is a very suitable treatment option for the older adult. When evaluating the literature on toxicity in older patients, it's important to recognise that older studies do not represent modern day radiotherapy techniques and capabilities. Advanced technology may simultaneously deliver enhanced target coverage and reduced toxicity. More research is required related to the predictive power of CGA in linking radiotherapy toxicity to frailty. What little evidence exists shows that CGA has a role in treatment of older patients with radiotherapy and that, in general, radiotherapy appears to be well tolerated in older adults. The purpose of this review is to provide a broad overview of the mechanisms of normal tissue reactions to radiotherapy and how radiation induced toxicity may affect older patients.